The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0078077
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Ubiquitin-Mediated Pathway of Arthropod Disease Vectors

Abstract: Protein regulation by ubiquitin has been extensively described in model organisms. However, characterization of the ubiquitin machinery in disease vectors remains mostly unknown. This fundamental gap in knowledge presents a concern because new therapeutics are needed to control vector-borne diseases, and targeting the ubiquitin machinery as a means for disease intervention has been already adopted in the clinic. In this study, we employed a bioinformatics approach to uncover the ubiquitin-mediated pathway in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Another example noted in the study of Korneta et al (2012) is NOSIP (nitric oxide synthase interacting protein) (CG6179), which contains an Rtf2 domain and is a component of the Drosophila melanogaster spliceosome (Herold et al 2009). The Rtf2 domain has been annotated in association with RING E3 ubiquitin ligases (Choy et al 2013) and suggested to act as an ubiquitin ligase in the context of splicing (Korneta et al 2012). A divergent cyclophilin that may be involved in splicing also contains an Rtf2 domain (Page and Winter 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Another example noted in the study of Korneta et al (2012) is NOSIP (nitric oxide synthase interacting protein) (CG6179), which contains an Rtf2 domain and is a component of the Drosophila melanogaster spliceosome (Herold et al 2009). The Rtf2 domain has been annotated in association with RING E3 ubiquitin ligases (Choy et al 2013) and suggested to act as an ubiquitin ligase in the context of splicing (Korneta et al 2012). A divergent cyclophilin that may be involved in splicing also contains an Rtf2 domain (Page and Winter 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that other classes of E3s can be involved in releasing additional HDPs. In fact, the results summarized in Table 2 show that other HECT-containing E3s also produce functional peptides, such as HECW1 and HECW2; therefore, it is likely that other E3s can mediate the production of functional peptides, consistent with the low numbers of HECT-containing ligases in arachnid genomes (63). Indeed, while Nedd4 or Nedd4-2-deficient mice show a variety of phenotypes including embryonic and neonatal lethality (60), recent studies provided evidence that other classes of E3s (RING-containing) play a role in arachnid host defense, at least against the bacterial pathogen Anaplasma phagocytophilum (6466), as suggested by silencing the E3 ligase XIAP in I. scapularis ticks (64).…”
Section: Discussionmentioning
confidence: 83%
“…In this case, due to no difference between thresholds, results from the e-value 0.1 cutoff was selected for further analysis. A total of 1,229 UPPs in H. sapiens have been analyzed previously with a cutoff of 0.5 e-value using HMM search 23 . While we report 1,227 UPP proteins in H. Sapiens (see Table 1 ), this is consistent with reported data sets.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four Pfam motifs found in ubiquitin proteasome system were selected and downloaded from Pfam HMM library version 22.0 44 . The following Pfam domains were included Ufm1, PF03671; APG12, PF04110; Atg8, PF02991; ubiquitin, PF00240; Urm1, PF09138; ThiF, PF00899; UBACT, PF02134; UQ-con, PF00179; zf-C3HC4, PF00097; zf-RING-like, PF08746; zf-MIZ, PF02891; HECT, PF00632; Cullin, PF00888; U-box, PF04564; F-box, PF00646; OTU, PF02338; Josephin, PF02099; JAB, PF01398; DUF862, PF05903; WLM, PF08325; UCH, PF00443; Peptidase C12, PF01088; Peptidase C48, PF02902; and Peptidase C54, PF03416 23 , 24 .…”
Section: Methodsmentioning
confidence: 99%